Food Preference, Foraging Activity, Inter- And Intraspecific Aggression And Baiting Of The Crazy Ant, Paratrechina Longicornis (Latreille) (Hymenoptera: Formicidae) - Sam , Siao Jing (2010)

(untitled)
This thesis focuses on the study of food preferences, foraging activity, interand intraspecific interactions as well as baiting of Paratrechina longicornis (Latreille). Amongst all the carbohydrate and lipid foods, P. longicornis preferred saccharose sugar and egg yolk (P < 0.05) the most. Crazy ant also highly preferred dried anchovy and it was significantly (P < 0.05) preferred over the other candidates except dried prawn, tuna fish and sausage. This species are also more attracted to lower viscosities but higher concentrations of food (P < 0.05). Besides that, P. longicornis favoured their diet in liquid solution as well as protein and lipid food in solid form (P < 0.05). In contrast, semi-solid food was less appeal to these ants (P > 0.05). P. longicornis preferred relatively large food particles but not above 1900 μm in size. Foraging activity of P. longicornis was influenced more by ambient temperature compared to relative humidity. In addition, rain would affect the foraging activity of ants in varying degree depending on the duration and intensity of rainfall. Two peaks of activity were recorded, on between 5.00-7.00 pm and the other between 1.00-5.00 am.